The role of magnesium in cardiac arrest - Liu, Baoshan; Li, Muyuan; Wang, Jian; Zhang, Fengli; Wang, Fangze; Jin, Caicai; Li, Jiayi; Wang, Yanran; Sanderson, Thomas Hudson; Zhang, Rui (Frontiers in Nutrition, 2024)
Cardiac arrest is a leading cause of death globally. Only 25.8% of in-hospital and 33.5% of out-ofhospital individuals who achieve spontaneous circulation following cardiac arrest survive to leave the hospital. Respiratory failure and acute coronary syndrome are the two most common etiologies of cardiac arrest. Effort has been made to improve the outcomes of individuals resuscitated from cardiac arrest. Magnesium is an ion that is critical to the function of all cells and organs. It is often overlooked in everyday clinical practice. At present, there have only been a small number of reviews discussing the role of magnesium in cardiac arrest. In this review, for the first time, we provide a comprehensive overview of magnesium research in cardiac arrest focusing on the effects of magnesium on the occurrence and prognosis of cardiac arrest, as well as in the two main diseases causing cardiac arrest, respiratory failure and acute coronary syndrome. The current findings support the view that magnesium disorder is associated with increased risk of cardiac arrest as well as respiratory failure and acute coronary syndrome.